Esophageal motility disorders in symptomatic patients and its relation to age - Ahmed Abdelghani; Alhosaeyn Ibrahim; El-Sayed El-Sayed; Mohammad El Sherbiny; Ahmed Al-Badry (BMC Gastroenterology, 2023)
Abstract Background Although swallowing disorders can impact individuals of any age, some are unique to the elderly, and others are frequent. Some disorders, such as achalasia, are diagnosed by esophageal manometry studies, which assess lower esophageal sphincter (LES) pressure and relaxation, peristalsis in the esophageal body, and contraction wave characteristics. This research aimed to evaluate esophageal motility dysfunction in symptomatic patients and its relation to age. Methods Conventional esophageal manometry was performed on 385 symptomatic patients who were divided into two groups; Group A (age < 65 years old) and Group B (age ≥ 65 years). The geriatric assessment for Group B included cognitive, functional, and clinical frailty scales (CFS). Additionally, a nutritional assessment was done for all patients. Results About one-third of the patients (33%) had achalasia, in which manometric results were significantly higher in Group B (43.4%) than in Group A (28.7%) (P = 0.016). The resting lower esophageal sphincter (LES) pressure, as determined by manometry examination, was significantly lower in Group A than in Group B. In contrast, complete LES relaxation percentage and normal esophageal body peristalsis were significantly higher in Group A than in Group B. Patients who exhibited evidence of achalasia in the manometric study had a significantly increased risk of established malnutrition and functional impairment. Conclusions Achalasia is a prevalent cause of dysphagia in elderly patients, placing them at risk of malnutrition and functional impairment. Thus, a multidisciplinary approach is vital when providing care for this population.